Biaya Article Processing Charges (APC): Studi Kasus Publikasi Artikel pada Jurnal Berdampak Tinggi - Wahyudin Darmalaksana (Gunung Djati Conference Series, 2026)
This study aims to examine Article Processing Charges (APC) in journal article publishing. This study employs a qualitative approach, utilizing the case study method. The findings indicate that global publishers set higher APC for high-impact journals using the open-access publishing model; however, they also offer a no-fee pathway—involving peer review, author revisions, and editorial acceptance—under a closed-access (subscription-based) model. The study concludes that APC are primarily targeted at competitive research projects supported by substantial funding to ensure high citation rates for published articles, whereas research findings intended for immediate public access can be uploaded to repositories as pre-prints, which do not incur APC.